2021
DOI: 10.1007/s00701-021-04816-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-injury antithrombotic agents predict intracranial hemorrhagic progression, but not worse clinical outcome in severe traumatic brain injury

Abstract: Background The incidence of traumatic brain injury (TBI) patients of older age with comorbidities, who are pre-injury treated with antithrombotic agents (antiplatelets and/or anticoagulants), has increased. In this study, our aim was to investigate if pre-injury antithrombotic treatment was associated with worse intracranial hemorrhagic/injury progression and clinical outcome in patients with severe TBI. Methods In this retrospective study, including 844 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Grandhi et al 26 found that antiplatelet agents did not influence neurosurgical intervention rates or mortality in patients ≥65 years old after closed HI. A 2021 retrospective study of 844 neurointensive care patients in Sweden27 did not show an association between antiplatelet use and mortality or poor outcomes after multiple regression analysis. In terms of studies included in this systematic review, Gangavati et al 15 found a reduced rate of tICH in patients on pre-injury clopidogrel and as there is not a biologically plausible mechanism for this the difference is likely due to confounding or bias that cannot be identified from the published information.…”
Section: Discussionmentioning
confidence: 94%
“…Grandhi et al 26 found that antiplatelet agents did not influence neurosurgical intervention rates or mortality in patients ≥65 years old after closed HI. A 2021 retrospective study of 844 neurointensive care patients in Sweden27 did not show an association between antiplatelet use and mortality or poor outcomes after multiple regression analysis. In terms of studies included in this systematic review, Gangavati et al 15 found a reduced rate of tICH in patients on pre-injury clopidogrel and as there is not a biologically plausible mechanism for this the difference is likely due to confounding or bias that cannot be identified from the published information.…”
Section: Discussionmentioning
confidence: 94%
“…tSAH volumes could not be calculated reliably and these lesions were only defined as present or absent. Hemorrhage progression of intracranial lesions was defined as an increase in EDH/ASDH/IVH/contusions with 6 mL or more, in accordance with previous studies [ 23 , 25 ]. Some patients received emergency neurosurgery immediately after the first CT and to take into account these different clinical trajectories of hemorrhage/injury evolution, the patients were divided into three groups: (1) stable intracranial hemorrhages on follow-up CT, (2) progression of intracranial hemorrhages on follow-up CT as defined above, (3) immediate intracranial surgery after the first CT. Midline shift (mm) and basal cisterns (open/compressed/obliterated) were assessed on both the 1st and 2nd CT.…”
Section: Methodsmentioning
confidence: 91%
“…Lastly, significant hemorrhage evolution has previously been defined in many different ways (e.g., absolute vs. relative increase in hemorrhage volume). We defined it as an absolute hemorrhagic increase with 6 mL, similar to Shin et al and a previous study by our group [ 23 , 25 ]. This threshold was set relatively high to really capture large and truly clinically significant hemorrhage progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-eight were selected for full-text analysis of which 19 were excluded as they did not fulfill the inclusion criteria. Finally, 20 studies were included in this review (16)(17)(18)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Characteristics of included studies are presented in Table 1.…”
Section: Details Of Search and Included Studiesmentioning
confidence: 99%